Prostaglandin treatment at the onset of norgestomet and estradiol-based synchronization protocols did not alter the ovarian follicular dynamics or pregnancy per timed artificial insemination in cyclic Bos indicus heifers - Sa Filho, M. F.; Marques, M. O.; Gimenes, L. U. [UNESP]; Torres-Junior, J. R. S.; Batista, E. O. S.; Carvalho, J. P. B.; Baruselli, P. S. (Elsevier B.V., 2014)
The aim of the present study was to evaluate the effects of the PGF(2 alpha) treatment given at the onset of a synchronization of ovulation protocol using a norgestomet (NORG) ear implant on ovarian follicular dynamics (Experiment 1) and pregnancy per AI (P/AI; Experiment 2) in cyclic (CL present) Bos indicus heifers. In Experiment 1, a total of 46 heifers were presynchronized using two consecutive doses of PGF(2 alpha) 12 days apart. At first day of the synchronization protocol the heifers received implants containing 3 mg of NORG and 2 mg of estradiol benzoate (EB). At the same time, heifers were randomly assigned to receive 150 mg of D-cloprostenol (n =23; PGF(2 alpha)) or no additional treatment (n =23; Control). When the ear implants were removed 8 days later, all heifers received a PGF(2 alpha) treatment and 1 mg of EB was given 24 h later. The follicular diameter and interval to ovulation were determined by transrectal ultrasonography. No effects of PGF(2 alpha) treatment on the diameter of the largest follicle present were observed at implant removal (PGF(2 alpha) =9.8 +/- 0.4 vs. Control = 10.0 +/- 0.3 mm; P=0.73) or after 24h (PGF(2 alpha) =11.1 +/- 0.4 vs. Control = 11.0 +/- 0.4 mm; P= 0.83). No differences in the time of ovulation after ear implant removal (PGF20 =70.8 +/- 1.2 vs. Control = 73.3 +/- 0.9 h; P=0.10) or in the ovulation rate (PGF(2 alpha) = 87.0 vs. Control =82.6%; P= 0.64) between treatments were observed. In Experiment 2,280 cyclic heifers were synchronized using the same experimental design described above (PGF(2 alpha); n=143 and Control; n=137), at random day of the estrous cycle. All heifers received 300 III of equine chorionic gonadotropin (eCG) and 0.5 mg of estradiol cypionate (as ovulatory stimulus) when the NORG ear implants were removed. Timed artificial insemination (TAI) was performed 48 h after implant removal and the pregnancy diagnosis was conducted 30 days later. No effects on the P/AI due to PGF(2 alpha) treatment were observed (PGF(2 alpha) =51.7 vs. Control =57.7%; P= 0.29). In conclusion, PGF(2 alpha) treatment at the onset of NORG-based protocols for the synchronization of ovulation did not alter the ovarian follicular responses or the P/AI in cyclic Bos indicus beef heifers synchronized for TAI. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Bovine; Hormonal therapy; Progesterone; Luteolysis; Nelore